Gender, diversity, and sustainable civil society strengthening: lessons from Ethiopia. Issue 5 (3rd July 2016) - Dawson, Elsa L.
ABSTRACT: This practical note explores how an awareness of gender and diversity issues can enable work in strengthening civil society to achieve lasting impact on the lives of women and men living in poverty. Understanding that people are poor because of their gender or diversity identity enables CSOs to be relevant. If work to strengthen civil society is to contribute to long-term social inclusion and greater social justice and equality, it must start from an analysis of who is excluded and why; here gender and diversity contextual analysis is indispensable, as is action on how civil society initiatives can help to level the playing field.